2015
DOI: 10.1128/jvi.01340-15
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter of the Biosphere: the Amazing World of Bacteriophage Diversity

Abstract: Bacteriophages are the most abundant biological entities in the biosphere, and this dynamic and old population is, not surprisingly, highly diverse genetically. Relative to bacterial genomics, phage genomics has advanced slowly, and a higher-resolution picture of the phagosphere is only just emerging. This view reveals substantial diversity even among phages known to infect a common host strain, but the relationships are complex, with mosaic genomic architectures generated by illegitimate recombination over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 20 publications
4
167
0
2
Order By: Relevance
“…The use of these methods to study virus diversity and biogeography in desert soils is relatively new and most commonly involves the sequencing of whole metaviromes (37)(38)(39). However, metaviromic approaches generally result in a large number of unknown sequences (43). In addition, we warn that the taxonomic affiliation of single genes and/or virus genome fragments (using BLAST analysis of public databases) in metavirome data sets may not be evidence for the presence of these viruses in the sample (80), and results should be carefully inspected by additional read mapping to a reference genome.…”
Section: Technical Recommendations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of these methods to study virus diversity and biogeography in desert soils is relatively new and most commonly involves the sequencing of whole metaviromes (37)(38)(39). However, metaviromic approaches generally result in a large number of unknown sequences (43). In addition, we warn that the taxonomic affiliation of single genes and/or virus genome fragments (using BLAST analysis of public databases) in metavirome data sets may not be evidence for the presence of these viruses in the sample (80), and results should be carefully inspected by additional read mapping to a reference genome.…”
Section: Technical Recommendations and Future Researchmentioning
confidence: 99%
“…With the advances in next-generation-sequencing (NGS) technologies, culture-independent methods have become the standard for determinations of viral diversity (41). However, the rapidly growing volume of viral environmental sequence data has revealed that most sequences (ϳ70%) have no homologs in public databases, and such sequences are typically labeled "viral dark matter" (42,43). Here, we discuss the current understanding of hot and cold desert soil virus diversity and function, propose alternative technical approaches to virus concentration methods, and identify key areas of future research.…”
mentioning
confidence: 99%
“…Each architectural type defines the structural basis of a lineage. Whether this approach can ultimately succeed has been discussed previously at length, but with no clear resolution (1419), leading us to seek further support from sequence-based analysis and to compare our results with the structural data, although the identification of viral proteins from sequences alone is known to be very challenging due to the overwhelming size and diversity of the virosphere (1, 3, 20, 21). Here, our primary focus will be on the two most established structure-based viral lineages, roughly corresponding to the two supermodules recently identified using gene and genome network analysis (22).…”
Section: Introductionmentioning
confidence: 98%
“…Comparative genomic analysis of phages clearly shows them to have modular structures, with segments assembled to form distinct genomes (35, 75). This is evident at the nucleotide sequence level when comparing phages grouped within particular clusters or subclusters, where otherwise closely related segments are interspersed with regions that are unrelated or more distantly related.…”
Section: Insights Into Phage Evolutionmentioning
confidence: 99%